Understanding Mechanisms that Maintain Social Anxiety Disorder in Autistic Individuals Through the Clark and Wells (1995) Model and Beyond: A Systematic Review - Lei, J; Mason, C; Russell, A; Hollocks, MJ; Leigh, E (Springer, 2024)
Given the high co-occurrence of social anxiety in autism, no reviews to date have explored how cognitive and behavioural mechanisms identified to maintain social anxiety in non-autistic individuals may operate in autistic individuals. This systematic review evaluated: (1) empirical evidence underlying the Clark and Wells (1995) Cognitive Model of Social Anxiety in autistic individuals; (2) how vulnerability factors identified from autism literature (beyond core autistic traits) may be associated with social anxiety beyond the cognitive model. Published peer-reviewed English articles until 27th November 2023 were retrieved from PubMed, EMBASE, Ovid MEDLINE and PsycINFO. Quality appraisal and risk of bias were assessed using The Standard Quality Assessment Criteria for Evaluating Primary Research papers from a Variety of Fields tool. 47 articles met full inclusion criteria and included autistic individuals (with clinical diagnosis), a measure of social anxiety, and a mechanism outlined by either (or both) research questions. The majority of the 3340 participants across studies were male without intellectual disability, White/Caucasian, with 7 studies reporting an average age above 30 years old. Most studies used only self-report measures that may have inflated associations observed between social anxiety and mechanisms. All studies employed cross-sectional design, and no causality inferences could be drawn. Methodological issues around potential construct overlaps between social anxiety and autistic traits are highlighted. Overall, there is evidence in support of the as reported by Clark and Well (in: Heimberg (eds), A cognitive model of social phobia, The Guilford Press, 1995) model, as greater fear of negative evaluation from others, use of safety behaviours and somatic symptoms, and peer victimisation were associated with greater social anxiety. The review contributes evidence in support of autism specific contextual, predisposing/antecedent and maintenance factors of social anxiety beyond the original Clark and Well (in: Heimberg (eds), A cognitive model of social phobia, The Guilford Press, 1995) model. Given the potential for considerable heterogeneity for each highlighted process at an individual level across autistic individuals, clinicians can broaden formulation conversations with autistic clients to understand how autism related factors may influence the development and maintenance of social anxiety symptoms when applying and adapting the Clark and Well (in: Heimberg (eds), A cognitive model of social phobia, The Guilford Press, 1995) model.